2017
DOI: 10.1186/s12879-017-2812-z
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus in semen and the risk for male infertility: a systematic review and meta-analysis

Abstract: BackgroundHuman papillomavirus (HPV) is one of the most prevalent sexually transmitted viruses. Despite the increasing evidence of HPV prevalence in semen, the worldwide distribution of HPV types in semen and risk for male infertility remain inconclusive.MethodsFour electronic databases were searched for English language studies conducted between January 1990 and December 2016 that reported HPV DNA prevalence in semen. Based on the PRISMA guidelines, HPV prevalence was estimated among general population and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 53 publications
5
87
0
5
Order By: Relevance
“…The role of the father and other caregivers as a transmitter is not clear. Semen may be a vector for HPV transmission, as well [41-43]. …”
Section: Other Possible Transmission Routes Of Hpv Infectionmentioning
confidence: 99%
“…The role of the father and other caregivers as a transmitter is not clear. Semen may be a vector for HPV transmission, as well [41-43]. …”
Section: Other Possible Transmission Routes Of Hpv Infectionmentioning
confidence: 99%
“…Although previous meta-analyses have established an association between HPV infection and both male infertility (Lyu et al, 2017) and the outcomes of natural or IVF/ICSI pregnancies (Siristatidis et al, 2018;Xiong et al, 2018), little is known regarding its role in female infertility. This is thought to be the first meta-analysis of studies comparing the prevalence of HPV infection in the infertile and general female population.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning HLA‐DQB1*03:01 allele, identified as a risk factor for OLI, previous studies showed conflicting results: Whereas in chronic hepatitis, this allele has been correlated in some instances with HCV clearance (Huang et al ., ; Thio et al ., ; El‐Bendary et al ., ), other authors have reported a link between HLA‐DQB1*03:01 and HPV6 infection (Chen et al ., ). Notably, this HPV subtype, despite being considered as low risk for cervical cancer, is established to cause genital lesions and to be found in the semen (Lyu et al ., ; Flores‐Díaz et al ., ). In our cohort, no association of HLA‐DQB1*03:01 with HPV was not detected.…”
Section: Discussionmentioning
confidence: 99%